2006
DOI: 10.1021/nl061650p
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Localized Intense Optical Fields in Single Gold−Nanoparticle Assemblies and Ultrasensitive Raman Active Sites

Abstract: We demonstrate visualization of localized intense electromagnetic fields in real space in well-tailored dimeric and trimeric gold nanospheres by using near-field optical techniques. With two-photon induced luminescence and Raman measurements, we show that the electric field is confined at an interstitial site in the aggregate. We also demonstrate optical switching operations for the electric-field localized sites in the trimer structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
200
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 227 publications
(217 citation statements)
references
References 37 publications
16
200
0
1
Order By: Relevance
“…To date, investigations of the optical properties of LSPR have largely relied on far-field spectroscopic techniques or numerical simulations. Several experimental approaches have been utilized to visualize the near field, including scanning photoionization microscopy, 16,17 scanning near-field optical microscopy, [18][19][20][21] nonlinear luminescence or fluorescent microscopy, 22,23 nonlinear photopolymerization 24,25 and near-field ablation of a substrate. [26][27][28][29] However, these approaches have practical limitations; specifically, both scanning photoionization microscopy and scanning near-field optical microscopy require a scanning process to acquire a near-field image, and their spatial resolution barely reaches the sub-50-nm level.…”
Section: Introductionmentioning
confidence: 99%
“…To date, investigations of the optical properties of LSPR have largely relied on far-field spectroscopic techniques or numerical simulations. Several experimental approaches have been utilized to visualize the near field, including scanning photoionization microscopy, 16,17 scanning near-field optical microscopy, [18][19][20][21] nonlinear luminescence or fluorescent microscopy, 22,23 nonlinear photopolymerization 24,25 and near-field ablation of a substrate. [26][27][28][29] However, these approaches have practical limitations; specifically, both scanning photoionization microscopy and scanning near-field optical microscopy require a scanning process to acquire a near-field image, and their spatial resolution barely reaches the sub-50-nm level.…”
Section: Introductionmentioning
confidence: 99%
“…Imura et al observed field enhancement in interstitial gaps between nanoparticles by aperture NSOM technique [37]. They investigated Raman spectra and two-photon-induced photoluminescence (TPI-PL) at single dimeric and trimeric aggregates of gold nanospheres by employing Ti:Saphhhire laser (λ = 785 nm).…”
Section: Gap Mode Enhancementmentioning
confidence: 99%
“…We applied nearfield imaging to assembled gold nanoparticles and succeeded in experimental visualization of localized enhanced optical fields for the first time. 25,26 I felt that this finding might also stimulate a novel research area, as in the standing wave observation of a single nanoparticle mentioned above, and made some efforts to develop the study. As a result we have derived some guidelines for the structures of nanoparticle assemblies to get efficient field enhancement.…”
Section: Introductionmentioning
confidence: 97%
“…Figure 9 shows near-field two-photon excitation images for gold nanosphere dimers using a femtosecond Ti:sapphire laser (wavelength 780 nm) as an excitation source. 25,26 In this measurement the system is illuminated by the near-field radia- AWARD ACCOUNTS Bull. Chem.…”
mentioning
confidence: 99%